Ecological rehabilitation of a riparian ecosystem: case of a section of the Maravilla river in Jiménez of Cartago, Costa Rica - Bonilla-Villalobos, Verónica (2025)
[Introduction]: Over the last 20 years, Latin American tropical forests have decreased by 25 %, affecting biodiversity, ecosystem services, and water resources. The Maravilla River micro-watershed, located in Jiménez, Cartago, Costa Rica, faces deforestation due to monocultures and cattle ranching, increasing the risk of flooding. [Objective]: To develop an ecological rehabilitation process in the Maravilla River protection area to restore its ecological functionality, productivity, and local biodiversity. [Methodology]: This research was conducted between 2021 and 2023 and included field surveys, ecosystem services analysis, multicriteria evaluation, and delineation of protection areas. Criteria such as accessibility, lack of forest vegetation cover, recreational use, and compliance with protection regulations were considered. A total of 137 species and 49 plant families with restoration potential were identified, and various techniques were implemented for species establishment. [Results]: A significant recovery of vegetation was evidenced by the planting of 1 828 trees, 3 483 shrubs, 342 herbaceous plants, and 7 lianas. Techniques including live fencing, direct seeding, zigzag methods, and the tresbolillos method proved effective in controlling disruptive agents, increasing connectivity, attracting biodiversity, and improving soil conditions. [Conclusions]: The study highlights the importance of using species adapted to local conditions and involving the community to ensure the sustainability of rehabilitation efforts. [Recommendations]: Continue developing educational programs to foster community participation and maintain monitoring and maintenance of rehabilitated areas. Additionally, it is suggested to strengthen inter-institutional collaboration and cooperation with NGOs to expand ecological restoration efforts.